Analysis of the Effect of Education and Training on Employee Performance at PT PLN NP UPDK Pandan - Teguh Wahyono; Fadhlal Nugraha (International Journal of Management, Economic and Accounting, 2023)
This study aims to examine the effect of education and training on employee performance at PT PLN NP UPDK Pandan. The method used in this study is simultaneous hypothesis testing (F test) and partially (t test). The results of simultaneous regression model testing show that education and training variables together have a significant influence on employee performance, with an F value of 310.206 and a significance of 0.000. This suggests that hypotheses suggesting a significant influence between education and training on employee performance are acceptable. However, the test results partially showed that the education variable (X1) had no effect and was not significant on employee performance, with a significance value of 0.158. This means that the hypothesis that education influences employee performance is unacceptable. Meanwhile, the training variable (X2) was shown to have a positive and significant effect on employee performance, with a significance value of 0.000. The hypothesis that there is an effect between training and employee performance is acceptable. The results of the analysis showed that education did not have a significant effect on employee performance. However, training is proven to have a positive and significant influence on employee performance over other employees. This research provides a better understanding of the effect of education and training on employee performance at PT PLN NP UPDK Pandan. The results of this research can be used as a reference in the development of more effective education and training programs to improve employee performance in the company.